The Effectiveness of Capitation Fund Management for the National Health Insurance Program (JKN) at Health Clinics in Surabaya: - - Ary Rahmat HIDAYAT; Bayquni BAYQUNI; Marlini ALIANITA (International Journal of Environmental, Sustainability, and Social Science, 2025)
The development of the health sector in Indonesia, particularly through the National Health Insurance Program (JKN), aims to provide equitable and quality healthcare access for all citizens. However, the effectiveness of capitation fund management within JKN at Primary Health Facilities (FKTP) still faces various challenges, especially in East Java Province. This study focuses on analyzing the effectiveness of capitation fund management at PT. Kimia Farma Diagnostika's Jatim 1 Business Unit clinics, emphasizing aspects of direction, control, accountability, efficiency, and coordination. The research employs a qualitative descriptive approach with a case study design, involving in-depth interviews, observations, and documentation studies. The findings indicate that capitation fund management at FKTP is not yet optimal, hindered by issues such as planning that is not based on actual needs, weak internal oversight, and low managerial capacity. This study aims to provide significant contributions to the development of regional-based health financing governance models and enhance the effectiveness of JKN implementation in Indonesia. With a better understanding of capitation fund management, it is hoped that JKN's objective of providing quality health guarantees for all citizens can be optimally achieved. This research not only offers practical recommendations for Klinik Kesehatan di Surabaya, Jawa Timurbut also for other stakeholders in efforts to improve the overall effectiveness of the JKN programme.